Persephone the daring - Holub, Joan; Williams, Suzanne, 1953- (Holub, Joan. Goddess girls, 2013)
Orpheus is a mortal rock god, and the girls at Mount Olympus Academy are wild about him! With his lyre and singing voice, Orpheus can charm pretty much anything, even things like stones and trees. But Hades and the other MOA boys aren't charmed. In fact, they are less than thrilled that the girls are so gaga over this guy. His fans are especially excited about his latest song about the girl he loved and lost, Eurydice. Orpheus was devastated when he lost Eurydice to the Underworld, so he asks Persephone to help get her back. Though it means breaking some very serious Underworld rules, Persephone pushes Hades to return Eurydice to the living world. But restoring Orpheus's one true love might jeopardize Persephone's own chances with her biggest crush.